Syn-to post-rift topographic tectonique and sedimentary evolution of the west African transform margin - (:unkn) unknown (My University, 2016)
This PhD thesis presents the first source-to-sink study of the African Atlantic Equatorial margin. We established new Meso-Cenozoic paleogeographic and structural reconstructions, integrating the West African sub-continent and the Equatorial Atlantic Ocean, based on a new mapping method defining both erosion limits of preserved deposits and their minimum original extension. We show the evolution over 200 Myrs of the eroding (sources) and accumulating domains (sinks) at continental scale. We demonstrate in particular that during the Cretaceous, a large Saharan intracratonic basin was exporting sediments toward both the Tethys and the future Atlantic Equatorial Ocean. The fragmentation of this basin occurred in the Oligocene, by the growth of the Hoggar swell that isolated the present-day small residual depot-centers. The development of this specific "basin and swell" topography results from the superimposition of various deformation wavelength at continental scale combining a marginal upwarp along the equatorial margin and a hot spot swell. We then characterized, from the interpretation of seismic data and well logs, the segmentation of the Equatorial Atlantic passive margin and the stratigraphic architecture of the post-rift Upper Cretaceous sedimentary wedge. We show that the proximal parts of the Late Cretaceous sedimentary wedge are only preserved along divergent segments of the margin and not along transform segments. We interpret this differential preservation as the result of a greater uplift, during the early post-rift, in the proximal parts of the transform segments preventing the preservation of the proximal terms of the sedimentary systems. The transform segments are associated with narrow necking zone, resulting in greater flexural uplift than divergent segments showing wider necking zones, in particular during the early post-rift. The characterization of the stratigraphic architecture of the post-rift sedimentary wedge then allowed for the
Keywords: African Research